Model-based hierarchal control framework for frequency and voltage stability in islanded microgrids with low inertia - Girmaw Teshager Bitew; Teketay Mulu Beza; Muhammad Shahzad (APL Energy)
Islanded microgrids with high renewable energy penetration face critical challenges in maintaining frequency and voltage stability owing to their low system inertia, communication delays, and intermittent generation. This paper proposes a hierarchical control framework that integrates adaptive virtual synchronous generator (VSG) dynamics, a delay-compensated consensus protocol, and battery energy storage system (BESS) optimization. The framework adopts VSGs with dynamically adjustable inertia, combined with adaptive Q–V droop control, to coordinately regulate frequency and voltage while compensating for communication delays using predictive feedback and event-triggered mechanisms. A multi-objective BESS strategy achieves a balance among synthetic inertia support, voltage regulation, and state-of-charge (SoC) limitations. Simulation results for a 500 kW microgrid with 70% renewable energy show that the proposed framework outperforms conventional droop control and fixed-inertia VSGs. The main results include frequency deviation below 0.04 Hz (versus 0.12 Hz for droop control), voltage regulation error within ±1.2% (versus ±4.2% for droop control), and a 50% reduction in communication traffic. In the case of a 150 kW diesel generator loss, PV system slowdown, and load surge, the adaptive VSG reduced the stabilization time by 30% and maintained the SoC of the BESS in the range of 20%–80%. This approach effectively addresses the challenges posed by low inertia, enhances the physical resilience of the grid, and provides a scalable solution for microgrids dominated by renewable energy sources. Future research will focus on hardware-in-the-loop verification and cyber-attack-resilience integration.